Robotic enucleation of a solid pseudopapillary neoplasm in a 9-year-old girl - G. Spampinato; A. Pasqualetto; E. Santonocito; M. Palermo; G. Belfiore; A. Basile; A. Di Cataldo; V. Di Benedetto; M. Scuderi (World Cancer Research Journal, 2020)
Objective: Here we reported the case of a 9-year-old girl with no relevant past medical or surgical history. Solid pseudopapillary neoplasms (SPN) is a rare pancreatic tumor, which is often observed in females in their second or third decades, but it can also be found in pediatric age. It is considered a low-grade malignant epithelial neoplasm with low metastatic rate and surgical resection represents the treatment of choice with an excellent long-term prognosis.